Single serum progesterone measurement: a key diagnostic and prognostic tool in threatened abortion - Rahmatunnesa; Fatema, Kanij; Rahman, Mohammad Abdur; Parvin, Khaleda; Mishi, Mazriha Naeem; Johora, Umme (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Miscarriage represents a prevalent complication during pregnancy, often leaving both patients and healthcare providers grappling with the anxiety of distinguishing viable from nonviable pregnancies in a timely manner. Identifying a highly sensitive and specific biomarker for this purpose could greatly enhance early intervention strategies. Progesterone has emerged as a significant biomarker for early pregnancy failure. This study aims to assess the effectiveness of a single serum progesterone measurement in cases of threatened abortion and its correlation with pregnancy outcomes. Methods: Conducted at the Gynaecology and Obstetrics Department of Sir Salimullah Medical College and Mitford Hospital in Dhaka between January and June 2020, this cross-sectional study included 60 women. Group I consisted of 30 patients (6 to 12 weeks of gestation) with vaginal bleeding, while Group II comprised 30 women with normal viable pregnancies of the same gestational age. Results: The mean age was approximately 24.87±3.79 years in Group I compared to 23.7±4.19 years in Group II. Notably, the mean serum progesterone levels were significantly different, with Group I showing 51.02±30.77 ng/ml versus 80.39±20.68 ng/ml in Group II (p<0.05). At 22 weeks of pregnancy, 60.0% of patients in Group I and 100.0% in Group II had viable outcomes, which was statistically significant (p<0.05). A serum progesterone cut-off value of ≥61 ng/ml demonstrated an 86.7% sensitivity and 70.0% specificity for predicting threatened abortion. Conclusions: Serum progesterone levels significantly differentiate between cases of threatened abortion and normal pregnancies, establishing it as a reliable marker for early pregnancy failure.